Human Posture Monitoring device and system - Tan, Sze Ying (2022)
The purpose of this project is to develop a Human Posture Monitoring device for lumbar region that can be mounted on the backbone. The purpose of this study is to design and analyse pain detection system for the rehabilitation device using various sensors. The target of the user of this prototype is a user who work in office or heavy lifting. The device requires a smart phone application that been developed to control the device as automatic control. The sensors used are bend sensor or also known as flex sensor. This sensor is used to give reading to the ESP32 when user do it daily work. Beside that in this project also SD card module that record every reading received from the sensor. To follow the fast growth of the technology, this study also takes part in developing a monitoring system using Internet of Things (IoT). Phone application programs were heavily researched. The device uses MIT app inventor software with the aid of Bluetooth module in the ESP32. The IoT of the project can further enhance by giving further advance reading to the user which also can monitor their health using the apps and improving the GUI of the application to be friendly and interactive.